The creeping water bugs (Hemiptera: Heteroptera: Naucoridae) of China, with description of a new species - Xie, Tong-Yin; Liu, Guo-Qing (Zootaxa, 2015)
This paper provides description of a new species, Cheirochela grossa sp. nov. from Yunnan Province. Cheirochela tonkina Polhemus, Polhemus & Sites, 2008, Heleocoris bengalensis montandoni Lundblad, 1933 and Thurselinus scutellaris (Stål, 1860) are reported from China for the first time. The checklist and a key to the species of Naucoridae of China are given. Dorsal habitus photographs of the species are provided, accompanied by illustrations of male genitalic structures and female ventral aspect of posterior abdominal segments (new species).